2015
DOI: 10.1016/j.gca.2015.04.048
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pH, grain size, and organic ligands on biotite weathering rates

Abstract: Biotite dissolution rates were determined at 25°C, at pH 2-6, and as a function of mineral composition, grain size, and aqueous organic ligand concentration. Rates were measured using both open-and closed-system reactors in fluids of constant ionic strength. Element release was non-stoichiometric and followed the general trend of Fe, Mg > Al > Si. Biotite surface area normalised dissolution rates (r i ) in the acidic range, generated from Si release, are consistent with the empirical rate law:where k H,i refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 71 publications
8
91
1
Order By: Relevance
“…These values are reflective of the kinetic rate of dissolution, so that 1 represents the maximum rate of dissolution and 0 represents an inert state. In our formulation, grain boundaries dissolve 1 order of magnitude more rapidly than the mineral core, which is consistent with experimental work (Lüttge et al, 2013;Emmanuel, 2014;Bray et al, 2015).…”
Section: Modeling Rock Weatheringsupporting
confidence: 88%
“…These values are reflective of the kinetic rate of dissolution, so that 1 represents the maximum rate of dissolution and 0 represents an inert state. In our formulation, grain boundaries dissolve 1 order of magnitude more rapidly than the mineral core, which is consistent with experimental work (Lüttge et al, 2013;Emmanuel, 2014;Bray et al, 2015).…”
Section: Modeling Rock Weatheringsupporting
confidence: 88%
“…It has nevertheless been suggested that fluids can become supersaturated locally if they are isolated from the bulk fluid leading to mineral replacement reactions (e.g. Putnis 2009;Ruiz-Agudo et al, 2012;Bray et al, 2014Bray et al, , 2015.…”
Section: The Long-term Dissolution Behavior Of Forsterite At Earth Sumentioning
confidence: 99%
“…Weathering rates were expressed as element release rates, determined for each treatment in each experiment in mmol/m 2 of mineral surfaces [61,62]. The total amounts of calcium and potassium were calculated in irrigation and drainage waters, biomass, and soil exchange sites; then, the total release was determined by a simple mass balance of output minus input for all pools [30].…”
Section: Chemical Analysismentioning
confidence: 99%
“…Biotite tends to dissolve and transform easily in any acidic environment [61,[66][67][68], and increased dissolution rates have been demonstrated with the presence of organic acids, especially oxalate [61,69,70]. However, biotite persists in many soils, which indicates that biotite dissolution is incongruent in pH conditions common to soils and element release becomes diffusion-limited due to secondary phases/remnant silicate framework at the mineral surface [61].…”
Section: Element Release Ratesmentioning
confidence: 99%
See 1 more Smart Citation